Massive hard palate tumor removed with an electric knife - Monika Ratajek-Gruda; Piotr Osica; Anna Janas-Naze (Kazimierz Wielki University, 2017)
The article describes a case of a 70-year-old patient with a massive hard palate tumor removed with an electric knife.